(untitled) (Research, Society and Development, 2021)
Low back pain is classified as a very common musculoskeletal disorder, being one of the main causes that generate disabilities as it involves several triggering risk factors, among them we can mention postural habits, psychological factors, sedentary lifestyle, long periods of sitting and lack of physical exercise. In university students it is possible to find many of these factors due to the assiduous study routine, which end up impacting their quality of life. This study is a literature review aiming to investigate the prevalence of low back pain in college students. Articles written in national and international languages that have been published between the years 2012 to 2021 in the electronic databases Google Academic, MedLine, PubMed, sciELO were included. It was possible to observe that there was a high prevalence of low back pain in college students, most of the articles exposed had in common the involvement of more than half of the participants with complaints of low back pain, with the female gender being more affected.